Highly filled polyethylene/barium metaplumbate composites for lead acid bipolar battery application - Sterzyński, T.; Kubczak, M. (Polimery, 2022)
Barium metaplumbate (BMP) is proposed as a conducting filler of polymer composite materials, used for production of support of active materials in lead acid bipolar battery. The composites of BMP with polyethylene as a matrix polymer, were prepared by means of Brabender kneader mixer were the PE matrix was modified by an addition of a liquid crystal polymer PET/PHB with the aim to regulate the matrix viscosity. The BMP content in the composites was in the range between 92and 94 wt. %. The electrical resistivity of the composites was found to be significantly dependent on BMP content, and an increase of the Vicat temperature was also observed for the composites. A homogeneous distribution of the barium methaplumbate particles in the polyethylene matrix was established by the SEM observation.